PENGEMBANGAN BUKU REFERENSI BIOEKOLOGI BERDASARKAN KAJIAN STRUKTUR KOMUNITAS LUMUT EPIFIT DI TAMAN NASIONAL BROMO TENGGER SEMERU - Marinda Sari Sofiyana; Fatchur Rohman; Murni Saptasari (Universitas Islam Balitar, 2016)
This study aims to develop a reference book on the basis of a study on bioecology bryophyte community structure in Bromo Tengger Semeru National Park. This study used research and development design from Borg and Gall. Two kinds of reference books were developed in this study: biology reference book and ecology of bryophyte reference book. This study revealed that results of validation on book materials, graphics, language and preliminary testing indicated that the book was developed fulfilling standardized criteria of good reference book. There was no revision required to improve the books.